Admission of Hb S heterozygotes to a general hospital is relatively reduced in malarial areas. Issue 4 (August 1985) - Colombo, B; Felicetti, L
Abstract : A comparison between the frequency of Hb S heterozygotes in blood donors, outpatients, and inpatients of a general hospital carried out at the Maputo Central Hospital, Mozambique, where Plasmodium falciparum malaria is endemic, showed a statistically significant lower percentage of Hb S heterozygotes in the inpatient group. Evidence is thus provided that the protection given by Hb S to heterozygotes concerns not only malarial infection itself, but probably a wide spectrum of diseases to which persons who have a special resistance to P falciparum infection are less prone.